Mind-Game as Zeitgeist: Reading Hollywood, America, and Contemporary Times Through its Popular Culture (KULT_online, 2021)
Thomas Elsaesser’s posthumous publication The Mind-Game Film: Distributed Agency, Time Travel, and Productive Pathology unites 12 articles of his most influential and intriguing thoughts on contemporary complex Hollywood cinema. The book offers a kaleidoscopic view on the heterogeneous corpus of films that Elsaesser perceives as symptomatic of institutional, political, ideological, and socio-cultural concerns of America and the world. In this, Elsaesser does not merely analyze mind-game films, but canvases the U.S. American zeitgeist through its popular culture.